Keefektifan Media Pembelajaran Berbasis Multimedia Menggunakan Powerpoint Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Novi Wulandari; Haifaturrahmah; Syafruddin Muhdar; Nursina Sari; Yuni Mariyati; Saddam (Madako Elementary School, 2022)
This study aims to determine the effectiveness of multimedia-based learning media using powerpoint on the learning outcomes of elementary school students. This type of research is R&D (Research and Development). The method used by the researchers was the Barg and Gall model (1potency and problem, 2 data collection, 3 product design, 4 design validation, 5design revision, 6 product trials, 7 product revisions, 8 discharging trials, 9product revisions, 10mass production). This research is specifically to see the effectiveness of multimedia-based learning media using powerpoint. The results of the effectiveness of multimedia-based learning media using powerpoint from the N-Gain score obtained a score of 0.74%. So that it can be concluded that the use of multimedia-based learning learning media using powerpoints in the high category and is effective for improving the learning outcomes of elementary school students.